PENDIDIKAN KARAKTER DALAM LULLABY JAWA - Kamil, Achmad Muchammad (Universitas Sultan Ageng Tirtayasa, 2022)
AbstrakSeveral ethnic groups in Indonesia have traditional lullaby, including the Javanese, namely Tak Lela Ledhung. In general, this Javanese Lullaby text contains character education values. The purpose and formulation of the research problem is the value of character education in the lullaby lyrics of Tak Lela Ledhung. The results showed that the Javanese lullaby entitled Tak Lela Ledhung was a tradition that contained the hopes and prayers of parents for their children. The character education values contained in the Javanese lullaby entitled Tak Lela Ledhung, namely: the value of justice, the value of courage, the value of self-control, the value of a positive attitude, the value of hard work, the value of integrity, and the value of wisdom. The inculcation of values as contained in the lullaby needs to be preserved, especially from the family environment. Keywords: Character Education, Tak Lela Ledhung